Tamoxifen induces apoptosis and inhibits respiratory burst in equine neutrophils independently of estrogen receptors. Issue 2 (21st October 2018) - Olave, Carla; Alvarez, Pamela; Uberti, Benjamin; Morales, Natalia; Henriquez, Claudio; Folch, Hugo; Sarmiento, Jose; Moran, Gabriel
Abstract: Neutrophils play an important role in the exacerbation and maintenance of severe equine asthma; persistent neutrophil activity and delayed apoptosis can be harmful to surrounding tissues. Tamoxifen (TX) is a nonsteroidal estrogen receptor modulator with immunomodulatory effects and induces early apoptosis of blood and bronchoalveolar lavage neutrophils from horses with acute lung inflammation. This study investigated if the in vitro effects of tamoxifen are produced by its action on nuclear (α and β) and membrane (GPR30) estrogen receptors in healthy equine neutrophils. Results showed that TX inhibits neutrophil respiratory burst induced by opsonized zymosan in a dose‐dependent manner. Nuclear (17‐β‐Estradiol) and GPR30 cell membrane (G1) estrogen receptor agonists and their antagonists (ICI 182, 780 and G15, respectively) do not block or reproduce the effect of TX. Therefore, TX does not inhibit respiratory burst through estrogen receptors. TX (8.5 μM) also increased phosphatidylserine translocation, a marker of early apoptosis, which did not occur with any of the estrogen receptor agonists or antagonists. Thus, tamoxifen generates dose‐dependent inhibition of respiratory burst and increased early apoptosis in healthy equine neutrophils, independently of nuclear or membrane estrogen receptors. Further studies are necessary to explore the signaling pathways of tamoxifen‐induced ROS inhibition and phosphatidylserine translocation.